Cerebral Arterial Time Constant Recorded from the MCA and PICA in Normal Subjects - Kasprowicz, Magdalena; Czosnyka, Marek; Poplawska, Karolina; Reinhard, Matthias (Acta neurochirurgica. Supplement, 2016)
Cerebral arterial time constant (τ) estimates how quickly the cerebral arterial bed distal to the point of insonation is filled with arterial blood following a cardiac contraction. It is not known how τ behaves in different vascular territories in the brain. We therefore investigated the differences in τ of two cerebral arteries: the posterior inferior cerebellar artery (PICA) and the middle cerebral artery (MCA).Transcranial Doppler cerebral blood flow velocity (CBFV) in the PICA and left MCA along with Finapres arterial blood pressure (ABP) were simultaneously recorded in 35 young healthy volunteers. τ was estimated using mathematical transformations of pulse waveforms of ABP and the CBFV of the MCA and the PICA. Since τ is independent from the vessel radius, its comparison in different cerebral arteries was feasible. Mean ABP was 76.1 ± 9.6 mmHg. The CBFV of the MCA was higher than that of the PICA (59.7 ± 7.7 vs. 41.0 ± 4.5 cm/s; p < 0.000001). τ of the PICA was shorter than that of the MCA (0.15 ± 0.03 vs. 0.18 ± 0.03 s; p < 0.000001). The MCA-supplied vascular bed has a longer distal average length, measured from the place of insonation up to the small arterioles, than the PICA-supplied vascular bed. Therefore, a longer time is needed to fill it with arterial blood volume. This study thus confirms the physiological validity of the τ concept.